German Environmental Concerns on Carbon Offsetting and Reduction: How it Deals with European and International Rules? - Samuel CorbalÃ¡n ArÃ©valo (Faculty of law Udayana University, 2023)
This paper analyzes the international climate protection instrument Carbon Offsetting and Reduction Scheme for International Aviation (CORSIA), which is based on the International Civil Aviation Organization (ICAO) Assembly No. A39-3, and its relation to the European Union Emissions Trading System (EU-ETS) in aviation, which is based on Directive 2008/101/EC. It is still unclear whether or to what extent the already existing EU-ETS in aviation can continue due to CORSIA. Questions regarding the implementation, enforcement and practicability of the climate protection instruments remain. The aim of this paper is to present a comparative analysis of the two climate protection instruments. In particular, to explore the question of the legal relationship between CORSIA and the EU-ETS in aviation as well as the legal compatibility of the two climate protection instruments is essential. It will also explore how the European Union (EU) and especially Germany intends to implement CORSIA in parallel to the EU-ETS in aviation. Germany actively participates in international and European discussions and contributes towards harmonizing the implementation of CORSIA with the EU-ETS, however, implementing CORSIA raises environmental concerns and brings challenges due to conflicting European and international rules. Therefore, this paper explores how Germany manages these conflicts and strives to strike a balance between regional and global approaches to mitigate the environmental impact of aviation. This conceptual paper analyzes relevant international, European, German legal instruments and textbooks, journal articles, academic works, and reports.